Rekonstruksi Alat Musik Rebeb Gayo Pada Pembelajaran Rekonstruksi Alat Musik (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
One of the achievements in the subject of concepts, techniques, and the reconstruction of art tools and equipment in the Dance and Music Drama Education Study Program, Faculty of Teacher Training and Education, Syiah Kuala University, was to reconstruct one of the musical instruments. In this study, one of the musical instruments that will be reconstructed is the traditional musical instrument of the people of Aceh, especially Central Aceh, which is called the Rebeb Gayo musical instrument. One of the reasons for reconstructing the Gayo Rebeb musical instrument is because this musical instrument has long been extinct. So that through the reconstruction of the musical instrument, the Rebeb Gayo musical instrument can be returned which has long been extinct. So this can be an effort to preserve extinct musical instruments. This research method is an experiment, by looking at the results of experiments on making Rebeb Gayo musical instruments starting from the preparation of tools and materials, manufacturing methods, tone systems and techniques for playing Rebeb Gayo musical instruments. The results of the research produced the Rebeb Gayo musical instrument and it can be played well.